Polyurethane resin composition

By combining the polyurethane resin composition without foam stabilizer and surface adjuster, combining the ratio of polyisocyanate compounds, polyol compounds, trimerization catalysts, foaming agents and flame retardants, the problems of expansion and fire spread during heating are solved, the stability and safety of the polyurethane resin composition are achieved, and the construction cost is reduced.

CN118574866BActive Publication Date: 2025-03-11NIPPON AQUA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280089062.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-18
Publication Date
2025-03-11
Estimated Expiration
2042-01-18

AI Technical Summary

Technical Problem

When using polyurethane resin composition as the thermal insulation material, heating causes expansion, which may contact with the spark plug or discharge, causing fire to spread, and problems such as insufficient bonding and falling off during construction.

Method used

A polyurethane resin composition without foam stabilizing agent and surface adjusting agent is used, including a polyisocyanate compound, a polyol compound, a trimerization catalyst, a foaming agent and a flame retardant, and a foaming body that is not easily expanded is formed by adjusting the ratio and process.

Benefits of technology

It is achieved that it is not easy to expand during heating, avoid spark contact and discharge, ensure the stability and safety of thermal insulation materials, and reduce construction costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004947022330000021
    Figure BDA0004947022330000021
  • Figure BDA0004947022330000041
    Figure BDA0004947022330000041
  • Figure BDA0004947022330000161
    Figure BDA0004947022330000161
Patent Text Reader

Abstract

Provided is a polyurethane resin composition that is not easily expanded when heated. The polyurethane resin composition, which is used to form a foamed body of a heat insulating material constituting a building, contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a foaming agent, and a flame retardant, and does not contain a foam stabilizer and a surface conditioner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyurethane resin composition and the like used as a thermal insulating material for buildings. Background Art

[0002] For RC-structured and S-structured houses, spray rigid polyurethane foam insulation materials are often used to prevent condensation, provide insulation, and save energy.

[0003] In recent years, it is rare to have a fire caused by ignition of insulation materials due to inadequate construction management, etc. In addition, even if a general fire occurs, there is a possibility that the fire will transfer to the insulation material and cause spreading combustion.

[0004] In order to prevent the combustion of such polyurethane foam, fire-resistant coating (cement-based inorganic spraying materials, etc.) is sometimes applied, but the construction is time-consuming and there are problems such as insufficient adhesion to the polyurethane foam and peeling of the residue after the construction.

[0005] Therefore, as polyurethane resin compositions imparted with flame retardancy, polyurethane resin compositions disclosed in the following Patent Documents 1 and 2 are known.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6200435

[0009] Patent Document 2: Japanese Patent No. 6725606 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] In the exothermic test according to ISO-5660 for evaluating the flame retardancy of a polyurethane resin composition, a testing device called a cone calorimeter is used.

[0012] The cone calorimeter includes a cone heater disposed above a test body cut out to a predetermined size, and a spark rod provided between the test body and the cone heater.

[0013] In the heat release test according to ISO-5660, a combustible gas is generated from the test body by heating with a conical heater, and the combustible gas is ignited by the spark of a spark rod to cause combustion. The total heat release obtained by the combustion is measured by a prescribed measurement method, and the flame retardancy is evaluated according to the performance requirements shown in the following Table 1.

[0014] The performance requirements are established by the Japan Building Testing Laboratories and the Building Materials Testing Center as standards for compliance with the technologies specified in Article 2, Item 9 of the Building Standards Act, Article 1, Items 5 and 6 of the Enforcement Decree of the Building Standards Act, and Article 108, Item 2 of the Enforcement Decree of the Building Standards Act.

[0015] [Table 1]

[0016]

[0017] When conducting the exothermic test, there is a situation where the test body expands due to heating using the conical heater, and there is a situation where the expanded part of the test body contacts the spark plug, or there is a situation where discharge is confirmed even if the expanded test body does not contact the plug (hereinafter these phenomena are also referred to as "spark contact").

[0018] A test piece that has spark contact will not provide a valid result in accordance with ISO-5660, so the presence or absence of spark contact must be confirmed each time.

[0019] Furthermore, when the polyurethane resin composition is used as a heat insulating material, there is also a problem that the expansion due to heating applies pressure to interior materials (such as gypsum boards) provided around the heat insulating material, causing damage.

[0020] If the interior materials are damaged, the heat during the fire is easily transferred to the heat insulating materials, and thus the possibility of thermally affecting the exterior materials increases.

[0021] Therefore, one object of the present invention is to provide a polyurethane resin composition that is less likely to expand when heated.

[0022] Solutions for solving problems

[0023] In order to solve the above problems, the invention of this application adopts the following technical features: it is a polyurethane resin composition for forming a foamed body constituting an insulating material for a building, which contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a foaming agent and a flame retardant, and does not contain a foam stabilizer and a surface adjuster.

[0024] Effects of the Invention

[0025] According to the present invention, a polyurethane resin composition which is less likely to expand when heated can be obtained.

[0026] In a preferred embodiment of the present invention, a polyurethane resin composition can be obtained that does not cause spark contact even in an exothermic test in accordance with ISO-5660.

[0027] Furthermore, in a preferred embodiment of the present invention, a polyurethane resin composition can be obtained which, when used as a thermal insulation material for a building, does not expand beyond the gap between the thermal insulation material and the interior material and does not press and damage the interior material.

[0028] Furthermore, in a preferred embodiment of the present invention, by reducing the number of raw materials required for forming the polyurethane resin composition, it is possible to contribute to cost reduction. DETAILED DESCRIPTION

[0029] <1>Overall structure

[0030] The polyurethane resin composition of the present invention is used to form a foamed body constituting a heat insulating material for a building, and contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a blowing agent and a flame retardant, and does not contain a foam stabilizer and a surface conditioner.

[0031] The polyurethane resin composition of the present invention may also be constituted by further containing a mineral-derived material such as a clay mineral.

[0032] By separating the above composition into a polyisocyanate compound (first liquid) and other components (second liquid), spraying the two while mixing and spraying; mixing the two while spraying, etc., an insulating layer can be formed in a building.

[0033] <2>For various performance

[0034] The polyurethane resin composition of the present invention can have the following performance by adjusting the compounding of each material.

[0035] <2.1> Regarding non-flammability

[0036] The polyurethane resin composition of the present invention may have non-flammability specified by an exothermic test in accordance with the test of ISO-5660.

[0037] <2.1.1> For ISO-5660 test

[0038] In the exothermic test based on ISO-5660, a testing device called a cone calorimeter is used.

[0039] The cone calorimeter includes a cone heater disposed above a test body cut into a predetermined size, and a spark rod disposed between the test body and the cone heater. Combustible gas is generated from the test body by heating with the cone heater, and the combustible gas is ignited by sparks from the spark rod, thereby causing combustion. The total heat release obtained by the combustion is measured by a predetermined measurement method, and flame retardancy is evaluated based on the performance requirements shown in the following Table 2.

[0040] [Table 2]

[0041]

[0042] <2.2> Expansion during heating (maximum expansion length)

[0043] The polyurethane resin composition of the present invention can expand to such an extent that spark contact does not occur when the ISO-5660 test is carried out.

[0044] As a criterion for preventing spark contact, the maximum expansion length of the test piece in the height direction is set to be less than 8 mm, more preferably 2 mm or less.

[0045] With the above configuration, spark contact can be avoided and a result effective as an ISO-5660 test can be obtained.

[0046] <2.2.1> Method for measuring expansion

[0047] The following is a method for measuring the amount of expansion in the height direction of the above-mentioned test body.

[0048] (1) Before the exothermic test, the height position of the upper surface of the test body was marked in advance on the windshield frame provided on the front of the cone calorimeter.

[0049] (2) After the heat release test, the height from the marked position on the windshield frame to the highest position on the upper surface of the expanded test body was measured by visual inspection.

[0050] <2.3> Regarding density

[0051] The polyurethane resin composition of the present invention can set the density of the foam to 30 kg / m 3 above.

[0052] By setting the density of the foam to 30 kg / m 3 As described above, when used as a heat insulating material for buildings, a sufficient deformation suppression effect against impacts from other factors can be obtained.

[0053] <3>Polyisocyanate compounds

[0054] The polyisocyanate compound is a material used as a main agent in the polyurethane resin composition of the present invention.

[0055] Examples of the polyisocyanate compound include aromatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates, and modified polyisocyanates.

[0056] Examples of the aromatic polyisocyanate include phenylene diisocyanate, toluene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate.

[0057] Examples of the alicyclic polyisocyanate include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate.

[0058] Examples of the aliphatic polyisocyanate include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.

[0059] The modified polyisocyanate refers to an isocyanate group-terminated prepolymer obtained by reacting a polyisocyanate compound with a polyol component, and examples thereof include urethane-modified products, carbodiimide-modified products, urea-modified products, biuret-modified products, and allophanate-modified products.

[0060] The polyisocyanate compounds may be used alone or in combination of two or more.

[0061] In particular, polymethylene polyphenyl polyisocyanate (POLYMERIC MDI, CRUDE MDI) is preferred because it is liquid at room temperature and is easily available.

[0062] Examples of the polymethylene polyphenyl polyisocyanate include Milionate MR-200, MR-100, and MR-400 manufactured by Tosoh Corporation, Sumidule 44V20L and Desmodur 44V20L manufactured by Covestro AG, PM-200 and PM-400 manufactured by Wanhua Chemical, and PAPI27 and PAPI135 manufactured by DOW.

[0063] The amount of the polyisocyanate contained in the polyurethane resin composition is preferably such that the isocyanate index is 150 to 1000. When the isocyanate index is 150 or more, the flame retardancy becomes further improved, and when the isocyanate index is 1000 or less, the adhesion to the body or the like becomes good.

[0064] In particular, in the present invention, the isocyanate index is most preferably within the range of 400 to 600.

[0065] The isocyanate index is calculated from the equivalent ratio of the isocyanate group contained in the isocyanate component to the active hydrogen contained in the polyol component and water of the foaming agent.

[0066] [Isocyanate group] / [OH group] (molar ratio) × 100

[0067] <4>Polyol compounds

[0068] The polyol compound is a material used as a curing agent in the polyurethane resin composition of the present invention.

[0069] The polyol compound includes an ester polyol compound or an ether polyol compound and a combination thereof.

[0070] <4.1> Ester polyol compounds

[0071] Examples of the ester polyol compound include polymers obtained by dehydration condensation of polybasic acids and polyols, polymers obtained by ring-opening polymerization of lactones such as ε-caprolactone and α-methyl-ε-caprolactone, and condensates of hydroxycarboxylic acids and the above polyols.

[0072] Here, specific examples of the polybasic acid include adipic acid, azelaic acid, sebacic acid, terephthalic acid, isophthalic acid, and succinic acid. From the viewpoint of flame retardancy, terephthalic acid modification is preferred.

[0073] <4.2>Other polyol compounds

[0074] Examples of other polyol compounds include polylactone polyols, polycarbonate polyols, aromatic polyols, alicyclic polyols, aliphatic polyols, polymer polyols, and polyether polyols.

[0075] Examples of the polylactone polyol include polypropiolactone diol, polycaprolactone diol, and polyvalerolactone diol.

[0076] Examples of the polycarbonate polyol include polyols obtained by dealcoholization reaction of a hydroxyl group-containing compound such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, and nonanediol with diethylene carbonate, dipropylene carbonate, and the like.

[0077] Examples of the aromatic polyol include bisphenol A, bisphenol F, phenol novolac, and cresol novolac.

[0078] Examples of the alicyclic polyol include cyclohexanediol, methylcyclohexanediol, isophoronediol, dicyclohexylmethanediol, and dimethyldicyclohexylmethanediol.

[0079] Examples of the aliphatic polyol include ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, and hexylene glycol.

[0080] Examples of the polyvalent polyether polyol include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, 3,3-dimethylolheptane, diethylene glycol, dipropylene glycol, neopentyl glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, dimer acid diol, bisphenol A, bis(β-hydroxyethyl)benzene, benzyl alcohol, glycerol, trimethylolpropane The invention also relates to polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide and butylene oxide using low molecular weight polyols such as oxadiazine, pentaerythritol and sucrose, or aromatic and aliphatic polyamines such as ethylenediamine, propylenediamine, toluenediamine, m-phenylenediamine, diphenylmethanediamine, xylylenediamine and triethanolamine as initiators, or by ring-opening polymerization of alkyl glycidyl ethers such as methyl glycidyl ether, aryl glycidyl ethers such as phenyl glycidyl ether, and cyclic ether monomers such as tetrahydrofuran.

[0081] In addition, polyether polyols containing bromine, phosphorus, etc. can also be used.

[0082] <5>Mineral-derived materials

[0083] The mineral-derived material is a material aimed at improving flame retardancy and density.

[0084] As the material derived from a mineral, a silicate compound is preferable. As the material derived from a mineral, for example, montmorillonite, saponite, hectorite, vermiculite, kaolinite, mica, talc, etc. can be used.

[0085] Examples of the material having kaolinite as a main component include kaolin.

[0086] The kaolin mentioned above also includes calcined kaolin obtained by treating kaolin at high temperature. Calcined kaolin is preferred from the viewpoint of small water content and particle size distribution.

[0087] The content of the mineral-derived material is not particularly limited, but is preferably 15 to 85 parts by weight based on 100 parts by weight of the polyol compound.

[0088] <6>Trimerization catalyst

[0089] The trimerization catalyst is a material for reacting and trimerizing isocyanate groups contained in the polyisocyanate compound to promote the formation of isocyanurate rings.

[0090] As a trimerization catalyst, for example, as a catalyst, nitrogen-containing aromatic compounds such as tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine, alkali metal salts of carboxylates such as potassium acetate, potassium 2-ethylhexanoate, potassium octoate, quaternary ammonium salts such as tetramethylammonium salt, tetraethylammonium, tetraphenylammonium salt, etc. can be used.

[0091] From the viewpoint of low-temperature adhesiveness and flame retardancy, a combination of an alkyl metal carboxylate and a quaternary ammonium salt is preferred.

[0092] Examples of the trimerization catalyst include Toyocat-TRX, Toyocat-TRV, and Toyocat-TR20 manufactured by Tosoh Corporation, DABCO TMR, DABCO TMR-2, DABCO TMR-7, DABCO K-15, UCAT 18X, and Polycat 46 manufactured by Evonik, and Kaolizer No. 410 and Kaolizer No. 420 manufactured by Kao.

[0093] The content of the trimerization catalyst is not particularly limited, but is preferably 1 to 20 parts by weight relative to 100 parts by weight of the polyol compound. When the content is 1 part by weight or more, the flame retardancy becomes further improved, and when the content is 20 parts by weight or less, the occurrence of problems such as clogging of the mixing part of the spray gun due to excessively rapid reaction can be suppressed.

[0094] <7> Foaming agent

[0095] The foaming agent is a material for promoting a decrease in the density of a molded product by generating gas inside the resin when the polyisocyanate compound (first liquid) and other components (second liquid) are mixed.

[0096] An example of a foaming agent is water. When isocyanate reacts with water, carbon dioxide is generated, and the carbon dioxide is introduced into the foam to promote the reduction of the density of the molded product.

[0097] Other examples of the foaming agent include the so-called physical foaming agents listed below. Although they are liquid at room temperature, they are gasified inside the resin by the exothermic reaction between the isocyanate and the polyol, and promote the reduction of the density of the molded product.

[0098] [1] Hydrocarbon compounds

[0099] Propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, cycloheptane, methyl formate, etc.

[0100] [2] Chlorinated aliphatic hydrocarbon compounds

[0101] Ethylene dichloride, propylene chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentane chloride, isopentane chloride, etc.

[0102] [3] Fluorine compounds

[0103] CHF3, CH2F2, CH3F, etc.

[0104] [4] Hydrochlorofluorocarbons

[0105] Trichloromonofluoromethane, trichlorotrifluoroethane, dichloromonofluoroethane (for example, HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), HCFC142b (1-chloro-1,1-difluoroethane)), and the like.

[0106] [5] Hydrofluorocarbons

[0107] HFC-245fa (1,1,1,3,3-pentafluoropropane) manufactured by Central Glass Co., Ltd., HFC-365mfc (1,1,1,3,3-pentafluorobutane) manufactured by Honeywell International Inc., and the like.

[0108] [6] Hydrofluoroolefins

[0109] Solstice LBA (HFO-1233zd, (E)-1-chloro-3,3,3-trifluoropropene) manufactured by Honeywell International Inc., Opteon 1100 (HFO-1336mzz(Z), (Z)-1,1,1,4,4,4-hexafluoro-2-butene) manufactured by The Chemours Company, Opteon 1150 (HFO-1336mzz(E), (E)-1,1,1,4,4,4-hexafluoro-2-butene) manufactured by The Chemours Company, Amorea 1224yd ((Z)-1-chloro-2,3,3,3-tetrafluoropropene) manufactured by AGC, etc.

[0110] [7] Organic compounds

[0111] Methyl formate, diisopropyl ether, etc.

[0112] In addition, as the foaming agent, nitrogen gas, oxygen gas, argon gas, carbon dioxide gas, etc. which can be dispersed or dissolved in the polyol component or the isocyanate component can also be used.

[0113] The content of the foaming agent is not particularly limited, but is preferably 1 to 100 parts by weight relative to 100 parts by weight of the polyol. The more parts by weight of the foaming agent, the lower the foam density, but at the same time, the lower the dimensional stability and compressive strength, so the parts by weight of the foaming agent that meet the density design can be set.

[0114] In the present invention, one or two or more of the above-mentioned foaming agents may be used.

[0115] <8>Flame retardant

[0116] The flame retardant is a material for imparting flame retardancy to the polyurethane resin composition of the present invention.

[0117] In the present invention, the flame retardant is not particularly limited, but a configuration containing at least one selected from the group consisting of red phosphorus, ammonium polyphosphate, and phosphoric acid ester is preferred from the viewpoint of obtaining high flame retardancy.

[0118] In particular, a configuration in which two or more of ammonium polyphosphate and phosphoric acid ester are combined in addition to red phosphorus is preferred from the viewpoint of obtaining a higher flame retardancy.

[0119] <8.1>Red phosphorus

[0120] Red phosphorus is a material used to suppress the total heat release during combustion.

[0121] The red phosphorus used in the present invention is not limited, and a commercially available product can be appropriately selected and used.

[0122] The content of the red phosphorus is not particularly limited, but is preferably 15 to 35 parts by weight based on 100 parts by weight of the polyol compound.

[0123] <8.2> Flame retardants containing phosphates

[0124] Phosphate-containing flame retardants are materials used to suppress the total calorific value during combustion, similarly to red phosphorus.

[0125] The phosphate-containing flame retardant used in the present invention contains phosphoric acid.

[0126] Examples of the phosphate-containing flame retardant include phosphates containing salts of the various phosphoric acids and at least one metal or compound selected from metals of Groups IA to IVB of the periodic table, ammonia, aliphatic amines, and aromatic amines.

[0127] Examples of the metals of Group IA to Group IVB of the periodic table include lithium, sodium, calcium, barium, iron (II), iron (III), and aluminum.

[0128] Examples of the aliphatic amine include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, and piperazine.

[0129] Examples of the aromatic amine include pyridine, triazine, melamine, and ammonium.

[0130] It should be noted that the phosphate-containing flame retardant may be subjected to known water resistance improvement treatments such as silane coupling agent treatment and melamine resin coating, or may contain known foaming aids such as melamine and pentaerythritol.

[0131] Specific examples of the phosphate-containing flame retardant include monophosphate, pyrophosphate, and polyphosphate.

[0132] Examples of the monophosphate include ammonium salts such as ammonium phosphate, diammonium phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as monomagnesium phosphate, magnesium hydrogen phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as monocalcium phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; and zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite.

[0133] Examples of the polyphosphate include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium polyphosphate amide, and aluminum polyphosphate.

[0134] Among them, in order to improve the self-flammability of the phosphate-containing flame retardant, it is preferred to use a polyphosphate, and more preferably to use ammonium polyphosphate or aluminum phosphite that forms a foaming layer when heated.

[0135] The phosphate-containing flame retardant may be used alone or in combination of two or more.

[0136] The content of the phosphate-containing flame retardant is not particularly limited, but is preferably 20 to 50 parts by weight based on 100 parts by weight of the polyol compound.

[0137] <8.3> Chlorine-containing flame retardants

[0138] The chlorine-containing flame retardant is an element for suppressing the maximum heat release rate in the initial stage of combustion.

[0139] The following five flame retardants are often used as chlorine-containing flame retardants.

[0140] (a) Tris(chloroethyl)phosphate (TCEP)

[0141] (b) Tris(β-chloropropyl)phosphate (TCPP)

[0142] (c) Tris(dichloropropyl)phosphate (TDCP)

[0143] (d) Tetrakis(2-chloroethyl)dichloroisopentyl diphosphate (V6)

[0144] (e) Polyoxyalkylene bis(dichloroalkyl) phosphate (CR-504L)

[0145] The content of the chlorine-containing flame retardant is not particularly limited, but is preferably 60 to 120 parts by weight based on 100 parts by weight of the polyol compound.

[0146] <9>For foam stabilizers and surface conditioners

[0147] The foam stabilizer and surface conditioner which are not included in the blending of the present invention will be described below.

[0148] <9.1> Foam stabilizer

[0149] The foam stabilizer is an organosiloxane-polyoxyalkylene copolymer or the like used in the production of polyurethane foam.

[0150] Examples of the foam stabilizer include L-6900 manufactured by Momentive and SH-193 manufactured by Dow Corning Toray Co., Ltd.

[0151] <9.2>Surface conditioning agent

[0152] Surface conditioners are additives that control surface tension and function as defoamers, leveling agents, and wrinkle preventers to form a good coating film.

[0153] Examples of the surface conditioner include acrylic polymers such as SEI-W01 and SEI-1501 manufactured by Kusumoto Chemical Industry Co., Ltd.

[0154] <10>Others

[0155] Furthermore, the polyurethane resin composition of the present invention may appropriately contain the following materials.

[0156] <10.1> Catalyst

[0157] The catalyst used in the formation of polyurethane foam is a material for promoting the reaction of isocyanate with active hydrogen in the polyol and the reaction of isocyanate with water.

[0158] Examples of the catalyst having an amine group include triethylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, N,N,N',N'-tetramethylethylenediamine and other N-alkyl polyalkylene polyamines, N'-(2-hydroxyethyl)-N,N,N'-trimethylethylenediamine, 1-(2-dimethylaminoethyl)-4-methylpiperazine, 1,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, N-methylmorpholine, N-ethylmorpholine, N,N-dimethylaminoethylmorpholine, dimethylcyclohexylamine, dimethylethanolamine, dimethylaminohexanol, dimethylaminoethoxyethanol, and diazabicycloundecene.

[0159] Examples of the organic metal-containing catalyst include bismuth octylate, lead octylate, tin(II) 2-ethylhexanoate, dibutylbis(octanoyloxy)stannane, dibutyltin diacetate, and dibutyltin dilaurate.

[0160] Examples of products of the amine catalyst include TEDA-L33, TOYOCAT-ET, TOYOCAT-MR, TOYOCAT-TE, TOYOCAT-DT, TOYOCAT-NP, RX-5, RX-10, and TOYOCAT-DM70 manufactured by Tosoh Corporation; DABCO 33LV, DABCO BL-19, DABCO BL-11, DABCO DMEA, DABCO T, DABCO N-MM, DABCO N-EM, DABCO XDM, DABCO NC-IM, Polycat 201, and Polycat 204 manufactured by Kao Corporation; and Kaolizer No. 1, Kaolizer No. 3, Kaolizer No. 10, Kaolizer No. 31, Kaolizer No. 21, Kaolizer No. 22, Kaolizer No. 25, and Kaolizer No. 26 manufactured by Kao Corporation. NO.26, KAOLIZER NO.120, KAOLIZER NO.300, KAOLIZERNO.350, KAOLIZERNO.390, etc.

[0161] These catalysts may be used alone or in combination of two or more.

[0162] Example

[0163] <1>Test conditions

[0164] The foam formed from the polyurethane resin composition of the present invention was subjected to the following tests. The detailed description of each material is as follows.

[0165] (1) Polyol compounds

[0166] A: terephthalic acid polyester polyol (manufactured by AIR WATER MATERIALS INC., product name: MAXIMOL RFK-505, hydroxyl value = 250 mgKOH / g)

[0167] (2) Foam stabilizer

[0168] B: Silicone foam stabilizer (Momentive, product name: L-6900)

[0169] (3) Surface conditioning agent

[0170] C: Acrylic polymer (manufactured by Kusumoto Chemical Industry, product name: SEI-W01)

[0171] (4) Catalyst

[0172] D1: Amine catalyst (manufactured by Evonik, product name: DABCO 2040)

[0173] D2: Amine catalyst (manufactured by Evonik, product name: Polycat 201)

[0174] D3: Organic metal catalyst (manufactured by SHEPHERD, product name: Bicat8210)

[0175] (5) Trimerization catalyst

[0176] E1: Quaternary ammonium salt (manufactured by Evonik, product name: TMR-7)

[0177] E2: Potassium acetate catalyst (manufactured by Evonik, product name: Polycat 46)

[0178] (6) Mineral-derived materials

[0179] F: Calcined kaolin (manufactured by Imerys Minerals, product name: Glomax LL)

[0180] (7) Flame retardant

[0181] G1: Red phosphorus (manufactured by Phosphorus Chemical Industry Co., Ltd., product name: Nova Excel 140)

[0182] G2: Ammonium polyphosphate (manufactured by Taihei Chemical Industry Co., Ltd., product name: TAIEN CII)

[0183] G3: Phosphate ester (manufactured by Wansheng, product name: TCPP)

[0184] (8) Foaming agent

[0185] H1: HFO-1233zd (manufactured by Honeywell International Inc., product name: Solstice LBA)

[0186] H2: HFO-1336mzz (manufactured by The Chemours Company, product name: Opteon 1100)

[0187] H3: Water (hydroxyl value = 6234 mgKOH / g)

[0188] (9) Polyisocyanate

[0189] I: POLYMERIC MDI (manufactured by TOSOH CORPORATION, product name: Milionate MR-200, NCO content = 31%)

[0190] <2>Test specimen preparation method

[0191] According to the compounding shown in the tables of the respective figures, the polyol, catalyst, trimerization catalyst, flame retardant, foaming agent, surface conditioner, and foam stabilizer components were weighed into a 1000 mL polypropylene beaker and stirred.

[0192] Hereinafter, this stirred product is referred to as a polyol premix.

[0193] The polyol premix and isocyanate were adjusted to 5°C.

[0194] For the temperature-controlled polyol premix component, add the isocyanate component according to the mixing table in each figure. After stirring with a hand mixer for about 3 seconds, quickly inject it into a 200×200×200mm wooden box that is temperature-controlled to 20°C to obtain a foam. (Since there is powder in the polyol premix component, it is pre-stirred and dispersed immediately before mixing with the isocyanate component.)

[0195] The foamed body that was aged for 24 hours after foaming was cut into a size of 99mm×99mm×50mm, and after measuring the mass (the foam density was calculated from the obtained mass and size), a cone calorimetry test body was prepared. (This test body was cut into a height of 50mm in the foaming direction.)

[0196] <3>Test content

[0197] For each test piece, a heat release test was performed in accordance with the test method of ISO-5660 at a radiant heat intensity of 50 kW / m 2 The heating time is set to 20 minutes, and the total heat release (10 minutes heating and 20 minutes heating), maximum heat release rate, and more than 200kW / m 2 Time (maximum heat release rate continuously exceeds 200kW / m2 The evaluation is carried out based on the time of the test piece, the maximum expansion length of the test piece (in the height direction), and the presence or absence of spark contact.

[0198] The detailed description of the test apparatus used in this test is as follows.

[0199] ·Toyo Seiki Co., Ltd., product name: Cone calorimeter Model: C4

[0200] ·Isolation length between test body and spark plug: 12.5mm

[0201] <4>Test results

[0202] The description will be given with reference to the respective figures of comparative experimental examples extracted from the entire test results.

[0203] (1) For Experimental Examples 1 and 2 (Table 3)

[0204] [When either a foam stabilizer or a surface conditioner is contained]

[0205] In Experimental Examples 1 and 2 (Table 3), either a foam stabilizer or a surface conditioner was contained.

[0206] [Table 3]

[0207]

[0208]

[0209] Any test body resulted in spark contact.

[0210] (2) Experimental Examples 3 to 21 (Tables 4 to 7)

[0211] [When the amount of kaolinite blended is changed]

[0212] In Experimental Examples 3 to 21 (Tables 4 to 7), no foam stabilizer and surface conditioner were contained, and the amount of kaolinite blended was changed from 0 to 100 parts by weight.

[0213] [Table 4]

[0214]

[0215]

[0216] [Table 5]

[0217]

[0218]

[0219] [Table 6]

[0220]

[0221]

[0222] [Table 7]

[0223]

[0224]

[0225] For any test body, the maximum expansion length was less than 2 mm and no spark contact occurred.

[0226] In addition, Experimental Examples 3, 4, 20, and 21 corresponded to quasi-noncombustible materials, and the test bodies of Experimental Examples 5 to 19 (the compounding amount of kaolinite was 15 parts by weight to 85 parts by weight) corresponded to noncombustible materials.

[0227] In the test bodies of Experimental Examples 4 to 21 (the amount of kaolinite blended was 10 parts by weight to 100 parts by weight), the foam density was 30 kg / m 3 above.

[0228] (3) For Experimental Examples 22 to 32 (Tables 8 to 10)

[0229] [When the amount of flame retardant compounded is changed]

[0230] In Experimental Examples 22 to 32 (Tables 8 to 10), a foam stabilizer and a surface conditioner were not contained, the blending amount of kaolinite was fixed at 25 parts by weight, and the blending amount of the flame retardant was changed.

[0231] [Table 8]

[0232]

[0233]

[0234] [Table 9]

[0235]

[0236]

[0237] [Table 10]

[0238]

[0239]

[0240] For any test body, the maximum expansion length was less than 2 mm and no spark contact occurred.

[0241] In addition, in the test bodies of Experimental Examples 23 to 26 and Experimental Examples 29 to 32, the foam density was 30 kg / m 3 above.

[0242] (4) Experimental Examples 33 to 40 (Table 11, Table 12)

[0243] [When the amount of foaming agent is changed]

[0244] In Experimental Examples 33 to 40 (Tables 11 and 12), no foam stabilizer and surface conditioner were included, and the amount of kaolinite blended was changed to 0 parts by weight, 25 parts by weight, 50 parts by weight, and 75 parts by weight, while the amount of each foaming agent blended was changed.

[0245] [Table 11]

[0246]

[0247]

[0248] [Table 12]

[0249]

[0250]

[0251] For any test body, the maximum expansion length was less than 2 mm and no spark contact was generated.

[0252] In addition, in Experimental Examples 33 and 40, it corresponds to a quasi-non-combustible material, and in Experimental Examples 34 to 39, it corresponds to a non-combustible material.

[0253] In addition, for any test body, the foam density is 30kg / m 3 above.

Claims

1. A polyurethane resin composition, characterized in that This is a polyurethane resin composition for forming a foamed body constituting a heat insulating material for a building, It contains at least a polyisocyanate compound, a polyol compound, a trimerization catalyst, a blowing agent, calcined kaolin and a flame retardant, and does not contain a foam stabilizer and a surface adjuster. The calcined kaolin is contained in an amount of 15 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the polyol compound. As the flame retardant, at least red phosphorus, ammonium polyphosphate and phosphate ester are contained, The isocyanate index is 400-600, and the density of the foam is 30 kg / m 3 above, The maximum expansion length in the height direction of a test body formed of the foamed body in a heat release test in accordance with ISO-5660 is 2 mm or less, and the test body corresponds to a non-combustible material.

Citation Information

Patent Citations

  • Production of 10,10-bis(4-hydroxyphenyl)-9-anthrone or derivative thereof

    JP1987000435A

  • Urethane resin composition and building insulation method

    CN112638970A

  • Expandable composition for non-flammable polyurethane foams

    CN113015757A